Institutional logics in women entrepreneurship : narratives of learning, struggles, and compromise from Dar es Salaam, Tanzania - Mwanga, Ombeni (2019)
This thesis explores institutional logics in women entrepreneurship in Dar es Salaam, Tanzania. It uses qualitative, narrative research methodology, and analyses different narratives from the women entrepreneurs on how they navigate their lives as women and as entrepreneurs. It brings about different stories from diverse experiences and encounters that they have gone through in the course of exploring entrepreneurship. The narratives were collected through 20 in-depth interviews conducted during the spring term of 2017. The data was based on their experiences as women entrepreneurs under MKUBWA program, which was facilitated by Tanzania Gatsby Trust in order to groom women entrepreneurs. After the data collection, the interviews which were conducted in Swahili were transcribed and thematically analyzed in dialogue with the institutional logics perspectives.